2021
DOI: 10.1080/00365521.2021.1906315
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide real-world study on dynamic ustekinumab dosing and concomitant medication use among Crohn’s disease patients in Finland

Abstract: Background: Real-world evidence to support optimal ustekinumab dosing for refractory Crohn's disease (CD) patients remains limited. Data from a retrospective nationwide chart review study was utilized to explore ustekinumab dosing dynamics and optimization, identify possible clinical predictors of dose intensification, and to evaluate ustekinumab trough concentrations (TCs) and concomitant medication use in Finland. Methods: Information gathered from17 Finnish hospitals included clinical chart data from 155 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…It has been reported that serum concentrations of UST are proportional to the dose and are associated with clinical efficacy [ 7 ]. A study from Finland revealed that 39% of patients with refractory CD required UST dose optimization by shortening the medication interval time [ 10 ]. However, the efficaciousness of the drug trough concentration and the adequate administration route are still debated worldwide [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that serum concentrations of UST are proportional to the dose and are associated with clinical efficacy [ 7 ]. A study from Finland revealed that 39% of patients with refractory CD required UST dose optimization by shortening the medication interval time [ 10 ]. However, the efficaciousness of the drug trough concentration and the adequate administration route are still debated worldwide [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, elevated baseline CRP was identified as an indicator of dose intensification in a recent real-world study of ustekinumab in patients with CD. 29 CL and V c in male patients were 17% higher than in female patients. Because body weight was already accounted for in the model, these effects may represent an additional layer of variability.…”
Section: Discussionmentioning
confidence: 70%
“…Among studies ONA that reported an initial maintenance dose ( n = 14), six reported a median of 29% of patients (range 9–100%) started on every-12-week dosing, while 13 out of 14 studies reported a median of 100% (range 63–100%) of patients initially started on every-8-week maintenance dosing (Fig. 2 ) [ 28 , 29 , 33 , 35 – 37 , 40 , 41 , 98 104 ]. The EMA recommendation, however, is to start with a lower dose regimen (e.g., 90 mg every 12 weeks) [ 105 ].…”
Section: Resultsmentioning
confidence: 99%